What is in a name and what is in the brain? -clinicians’ dilemmas in the biomarker era - Novotni, Gabriela; Karanfilska Plaseska, Dijana; Makazlieva, Tanja; Tanovska, Nikolina; Sibinovska, Olgica; Petlichkovski, Aleksandar; Novotni, Antoni (Elsevier BV, 2025)
This viewpoint draws analogy from Shakespeare’s query, "What’s in a name?" and explores what defines neurodegenerative diseases such as Parkinson’s (PD) and Alzheimer’s (AD) and what clinicians understand by that name in relation to the underlying brain pathology and disease biology. The inspiration comes from the latest biological definitions of PD revealing significant similarities with the biological definition of AD.